Eligibility, uptake and response to germline genetic testing in women with DCIS - Turza, Lauren; Lovejoy, Leann A.; Turner, Clesson E.; Shriver, Craig D.; Ellsworth, Rachel E. (Frontiers in Oncology, 2022)
Background Ductal carcinoma in situ (DCIS) is a malignant, yet pre-invasive disease of the breast. While the majority of DCIS have low risk of recurrence, a subset of women with germline pathogenic variants (PV) in cancer predisposition genes are at increased risk for recurrence. Uptake of genetic testing and subsequent surgical intervention in women with DCIS has not been well-studied. The aim of this study was to evaluate test eligibility parameters, uptake of clinical testing, impact on surgical decision making and second cancer events (SCE) in women with DCIS. Methods Four-hundred eighty-four women diagnosed with unilateral DCIS 2001-2020 were eligible for this study.. Demographic, commercial genetic test results and surgical procedures were extracted from the database. Test-eligibility was assigned using National Comprehensive Cancer Network (NCCN) criteria. Panel genetic testing was performed in the research laboratory across 94 cancer predisposition genes. Statistical analyses were performed using Fisher’s exact tests and Chi-square analyses with p < 0.05 defining significance. Results Forty-four percent of women were test-eligible at diagnosis of which 63.4% pursued genetic testing before definitive surgery; 9.9% pursued testing only after a second cancer event. Bilateral mastectomy (BM) was significantly higher (p<0.001) in women who had testing before definitive surgery (46.9%) compared to those who had testing afterword (10.8%) and in women who underwent testing before definitive surgery with PV (75%) compared to those without PV (37.5%. p=0.045). Of the 39 women with PV, 20 (51.3%) were detected only in the research setting, with 7 (17.9%) of these women not eligible for genetic testing based on NCCN criteria. In women who did not undergo BM at diagnosis, SCE were significantly higher (p=0.001) in women with PV (33.3%) compared to those without PV (11.9%). Conclusion Pursuit of genetic testing and subsequent use of risk-reducing surgeries in women with PV was suboptimal in women with a primary diagnosis of DCIS. In conjunction, >50% of PV were detected only in the research setting. Because omission of genetic testing in women with DCIS may represent a lost opportunity for prevention, genetic testing at the time of diagnosis should be standard for all women with DCIS.